Peningkatan Respons Imun Non Spesifik Ikan Gurame Pascapemberian Ekstrak Air Panas Mikroalga Spirulina platensis - Woro Hastuti Satyantini, ,- (Universitas Udayana, 2016)
Hot water extract of Spirulina platensis which is contain of lipopolysaccharide can be used as an immunostimulant. This study aimed to determine the effect of hot water extract of S. platensis through injection on the non-specific immune response of Osphronemusgouramy. The treatment was given through intraperitoneal injection of hot water extract of S. platensis with doses of 1%, 10%, 20% and PBS, Phosphate Buffer Saline (control) 0.1 ml/fish. Fish reared in the aquarium (67 l volune) with density 12 fishes/ aquarium with average weight of 7.5 – 8.5 g/fish. Blood samples of fish taken from the caudal vein on day 0 (before administration of the extract), 3 and 5 days after administration of the extract for the measurement of total leucocytes, differential leucocytes and phagocytic activity. Results showed an increased in total leucocytes, phagocytic activity, monocytes and neutrophils of fish that given hot water extract of S. platensis. The addition of hot water extract of S. platensis at 1% through injection gave total leucocytes, phagocytic activity, monocytes and neutrophils on days 3 were 543.73 x 103sel/mm3,69.30%, 34.33% and 14% respectively higher and significantly different to control.